2015
DOI: 10.1152/ajpheart.00567.2015
|View full text |Cite
|
Sign up to set email alerts
|

The stress of maternal separation causes misprogramming in the postnatal maturation of rat resistance arteries

Abstract: Reho JJ, Fisher SA. The stress of maternal separation causes misprogramming in the postnatal maturation of rat resistance arteries. Am J Physiol Heart Circ Physiol 309: H1468-H1478, 2015. First published September 14, 2015; doi:10.1152/ajpheart.00567.2015.-We examined the effect of stress in the first 2 wk of life induced by brief periods of daily maternal separation on developmental programming of rat small resistance mesenteric arteries (MAs). In MAs of littermate controls, mRNAs encoding mediators of vasoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 63 publications
0
11
1
Order By: Relevance
“…Exposure to MatSep during postnatal life is not associated with increased body weight or blood pressure at baseline; however, this model exerts a long-lasting effect on ANG II-induced vasoconstriction in adult rats fed an ND ex vivo (38) and in vivo (36,37), yet MatSep does not alter circulating levels of ANG II peptide, plasma renin activity, and aldosterone in ND-fed rats. Contrary to what we observed, Reho et al (48) has reported that the effects of MatSep on the vascular dysfunction trajectory wanes from postnatal to adult life. However, a large body of literature has shown that the sensitization of the cardiovascular response depends upon strain, stimuli, duration, and timing of the stressor or diet [reviewed in (44)].…”
Section: Discussioncontrasting
confidence: 99%
“…Exposure to MatSep during postnatal life is not associated with increased body weight or blood pressure at baseline; however, this model exerts a long-lasting effect on ANG II-induced vasoconstriction in adult rats fed an ND ex vivo (38) and in vivo (36,37), yet MatSep does not alter circulating levels of ANG II peptide, plasma renin activity, and aldosterone in ND-fed rats. Contrary to what we observed, Reho et al (48) has reported that the effects of MatSep on the vascular dysfunction trajectory wanes from postnatal to adult life. However, a large body of literature has shown that the sensitization of the cardiovascular response depends upon strain, stimuli, duration, and timing of the stressor or diet [reviewed in (44)].…”
Section: Discussioncontrasting
confidence: 99%
“…The effects of barren cage housing on NE and the sympathetic nervous system may be important in light of the current findings. Early life stress, as modeled by maternal separation during early development, induces a sensitization of the sympathetic nervous system (Loria et al 2013; Reho and Fisher 2015). For example, compared with controls, NE content is significantly increased in the spleen and adrenals of maternally separated offspring, and these rats display significantly greater increases in mean arterial pressure in response to NE administration, suggesting a sensitization of the sympathetic system by early life stress (Loria et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by studies in animal models showing that MS results in cardiac changes including cardiomyocyte hypertrophy as well as cardiac fibrosis [19]. More data is available showing that MS results in changes on the vascular level by misprogramming of resistance artery smooth muscles [20], increased vasoconstriction [21], and blood pressure [22,23]. These alterations are induced by superoxide production and endothelial dysfunction [24], inflammation [25], and sensitizing of the renal and sympathetic systems [26].…”
Section: Introductionmentioning
confidence: 86%